Identifying therapeutic compounds for autosomal dominant optic atrophy (ADOA) through screening in the nematode C. elegans - Fivos Borbolis; Palikaras, Konstantinos (Methods in cell biology, 2024)
Autosomal Dominant Optic Atrophy (ADOA) is a rare neurodegenerative condition, characterized by the bilateral loss of vision due to the degeneration of retinal ganglion cells. Its primary cause is linked to mutations in OPA1 gene, which ultimately affect mitochondrial structure and function. The current lack of successful treatments for ADOA emphasizes the need to investigate the mechanisms driving disease pathogenesis and exploit the potential of animal models for preclinical trials. Among such models, Caenorhabditis elegans stands out as a powerful tool, due its simplicity, its genetic tractability, and its relevance to human biology. Despite the lack of a visual system, the presence of mutated OPA1 in the nematode recapitulates ADOA pathology, by stimulating key pathogenic features of the human condition that can be studied in a fast and relatively non-laborious manner. Here, we provide a detailed guide on how to assess the therapeutic efficacy of chemical compounds, in either small or large scale, by evaluating three crucial phenotypes of humanized ADOA model nematodes, that express pathogenic human OPA1 in their GABAergic motor neurons: axonal mitochondria number, neuronal cell death and defecation cycle time. The described methods can deepen our understanding of ADOA pathogenesis and offer a practical framework for developing novel treatment schemes, providing hope for improved therapeutic outcomes and a better quality of life for individuals affected by this currently incurable condition.
Keywords: ADOA; C. elegans; Disease models; drug screening; Mitochondria; Neurodegeneration; Opa1